The Role of Blood Pressure, Diabetes Panel, Vitamin D, and Albumin in Sleep Quality Among the Elderly Population - Anastasia Ratnawati Biromo; Paskalis Andrew Gunawan; Alexander Halim Santoso; Bryan Anna Wijaya; Raden Seliwat Agung Aditya; Anthon Eka Prayoga Khoto (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Sleep disturbances are common among the elderly, influenced by multiple physiological factors, including blood pressure regulation, metabolic markers, nutritional status, and inflammation. Poor sleep quality has been linked to cardiovascular diseases, cognitive decline, and reduced overall well-being. Understanding the relationship between blood pressure, diabetes markers, vitamin D, and albumin levels with sleep quality may provide insights into potential interventions to improve sleep health in older adults. This study aims to analyze the correlation between blood pressure, diabetes panel (fasting blood glucose, fasting insulin, and HbA1c), vitamin D, and albumin levels with sleep quality in the elderly population. This Cross-sectional study was conducted at Bina Bhakti Nursing Home in 2024 to 58 elderly participants selected through total sampling. Sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI), while physiological parameters were measured using validated clinical and laboratory methods. Data were analyzed using Spearman’s Rho test to determine correlations between these factors and sleep disturbances. This study found that diastolic blood pressure and HbA1c level showed weak correlations with sleep quality. Low diastolic blood pressure and poor glycemic control demonstrated weak but statistically significant correlations with sleep quality among older adults. These findings indicate that certain physiological and metabolic factors, particularly diastolic blood pressure and HbA1c, may be associated with variations in sleep regulation among the elderly. Future research should explore targeted interventions, such as blood pressure management and metabolic regulation, that may improve sleep quality and overall health in the aging population.